CFD-based approaches for low-carbon shipping: A systematic review - Ranqi Ma; Zhiqiang Tang; Haoyang Zhao; Junhao Zhao; Rui Zhang; Zhuang Wang; Jianlin Cao; Yuhao Xie; Lianzhong Huang (Marine Pollution Bulletin, 2026)

A comprehensive evaluation of digestate gasification in biogas atmospheres towards the integration of anaerobic digestion and gasification - Rui Zhang; Zhuang Yuan; Hongru Li; Zhi Wang; Shengquan Zhou; Xiaochao Zhu; Zhanjun Cheng; Beibei Yan (Bioresource Technology, 2026)

A procedure for geostatistical inversion incorporating a high-resolution initial hydraulic-conductivity field from travel time inversion - Huiyang Qiu; Ning Luo; Yong Huang; Chao Zhuang; Xiaolan Hou; Walter A. Illman; Rui Hu (Journal of Hydrology, 2026)

Polysaccharide–metal complexes for precision nutrition: Intelligent delivery, gut microbiota modulation and gut–brain communication - Xiaoliang Zhang; Rui Tang; Zhi Wang; Hong Zhuang (Food Bioscience, 2026)

A Bayesian robust framework for estimating residential PM2.5 infiltration and indoor–outdoor contributions using paired low-cost sensors - Keqin Yang; Wenbin Zhuang; Rui You; Louise B. Weschler; Shu Wang; Charles J. Weschler; Jingya Wei; Ningrui Liu; Yinping Zhang (Building and Environment, 2026)

A numerical model for predicting bending behaviors of patch-repaired corroded RC structures considering longitudinal non-uniform corrosion - Hongwei Xie; Qinghua Li; Zhibin Zhuang; Rui Ma; Chaokun Hong; Shilang Xu (Engineering Structures, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

Co-regulatory roles of decaying logs and gap positions in modulating soil enzyme activities in forests ecosystems - Qin Wang; Josep Peñuelas; Zhuang Wang; Rui Cao; Lifeng Wang; Wanqin Yang (Plant and Soil, 2026)

Dynamic sulfidation process of nanoscale zero-valent iron induced by sulfate-reducing bacteria and its effect on the reductive dechlorination of trichloroethylene - Shaoyu Wan; Lijuan Zhang; Siqi Zhuang; Yi Su; Qi Liang; Rui Shen; Shanquan Wang; Andrei Ivanets; Bekchanov Davronbek; Xintai Su (Environmental Research, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Superposition Effects of Fire Exposure and Water Extinguishing on Fracturing Mechanisms and Mechanical Behavior of Granitic Building Stone - Fei Wang; Zhuang Xu; Heinz Konietzky; Liqiang Ma; Yu Pan; Qingyou Zhu; Rui Pang; Benguo He (Rock Mechanics and Rock Engineering, 2026)

Zinc and Iron(III) complexes of carboxymethyl Ganoderma polysaccharide: Chelation mechanism, structural features, and in vitro biological activity - Luyu Zhang; Xiaoliang Zhang; Xinyu Qi; Xiaolong Chen; Rui Zhao; Hong Zhuang (Food Bioscience, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Functional identity of typhoon-derived green litter overrides functional dissimilarity in reshaping litter faunal feeding guilds in a subtropical forest - Shuning Ma; Lifeng Wang; Qingjun Ma; Ajuan Zhang; Rui Cao; Zhuang Wang; Qin Wang; Mei Qin; Wanqin Yang (Plant and Soil, 2026)

Selenized Probiotic L. brevis 23017 Alleviates Colitis by Modulating the Nrf2-GPX4 Axis to Inhibit Ferroptosis - Yuxin Zhuang; Qiuju Liu; Fangfei Shi; Rui Kong; Chunli Ma; Dexing Ma (Biological Trace Element Research, 2026)

The role of personality in movement and reproductive differentiation in the termite Reticulitermes labralis - Yihang Xie; Chao Wang; Rui-Wu Wang; Zhuang-Dong Bai (Animal Behaviour, 2026)

A win-win recycling strategy for spent lithium-ion batteries: Prioritized selective lithium extraction afterwards triggers intrinsic catalysis - Yifan Sui; Zeqiu Chen; Yue Chang; Yaoguang Guo; Jie Guan; Xuning Zhuang; Fei He; Zhenming Zhang; Weihua Gu; Qianqian Chen; Li Fan; Qin Xu; et al. (Journal of Hazardous Materials, 2026)

Centrifuge modeling of static liquefaction in completely decomposed granite fill slopes - Zhun Liu; Yu Zhao; Teng Liang; Fan He; Rui Zhang; Zhuang Yan; Daosheng Ling; Liangtong Zhan; Yunmin Chen (Engineering Geology, 2026)

Simultaneous removal of sulfamerazine and nutrients in wastewater by alternate coupling of photocatalysis and microalgal system: From system construction to multi-interactions and purification effects - Lin-Lan Zhuang; Rui Li; Xiao-Xiong Wang; Yuxin Wu; Yanhui Zhao; Xiaojia Yi; Hongyang Liang; Weiyi Qian; Jian Zhang (Chemical Engineering Journal, 2026)

An earthworm-inspired hydrogel coating for hydration-assisted aqueous lubrication on diverse polymer substrates - Zhi-Guo Wang; Xi Liao; Yong-Jie Dan; Yu-Wei Liu; Yan-Hua Niu; Rui Hong; Ming Cai; Ju-Xiang Gou; Jia-Zhuang Xu; Zhong-Ming Li; Ka Li (Chemical Engineering Journal, 2026)

Soil bacterial and fungal communities beneath different forest types differentially and promptly respond to non-catastrophic typhoon disturbance - Zhihui Wang; Rui Zhang; Rui Cao; Lifeng Wang; Zhuang Wang; Qin Wang; Yuchen Lu; Yong Zhang; Wanqin Yang (Biology and Fertility of Soils, 2026)

UL24 deletion attenuates Marek's disease virus replication and pathogenicity - Yunzhe Kang; Xiuwen Yang; Rui Wang; Wenhui Zhu; Lulu Yao; Lijie Lv; Yongkun Du; Guoqing Zhuang; Aijun Sun (Veterinary Microbiology, 2026)

Resistant dextrin/xanthan gum gels protect probiotics for application to ionizing radiation shielding - Minting Wang; Rui Sun; Liuchan Zeng; Shumin Du; Yubao Fang; Bo Zhuang; Bochuan Yuan; Yiguang Jin (Food Research International, 2026)

Rewiring (p)ppGpp metabolism for high-yield anaerobic methanol and CO2 conversion in Butyribacterium methylotrophicum - Yuanke Guo; Feiyi Zhuang; Rui Zhang; Ruirui Qin; Jiao Feng; Kequan Chen; Xin Wang (Chemical Engineering Journal, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Study on flame retarding mechanism of 1,1,2,3,3,3-hexafluoro-1-propene - Rui Zhai; Jinkun Chen; Yongjie Shi; Yuan Zhuang; Xiang Li; Bin Ye; Lei Tang; Shancai Tang (Fuel, 2026)

How Chlorella vulgaris remove florfenicol from wastewater—— from the aspects of kinetics, mechanism, limiting factors and long-term regulation - Lin-Lan Zhuang; Kehan Zhou; Wanqing Tian; Rui Li; Yingdong Shi; Zhongzhong Wang; Jian Zhang (Water Research, 2026)

A unified hybrid deterministic-stochastic inversion methodology - Chao Zhuang; Long Yan; Huiyang Qiu; Rui Hu; Jiangbo Han; Huan Song; Zhifang Zhou; Jinguo Wang; Walter A. Illman (Journal of Hydrology, 2026)

Study on the flame inhibition characteristics and mechanism of R1233zd(E) - Rui Zhai; Zhijun Li; Yuan Zhuang; Bin Ye; Hongling Zhao; Lei Tang; Ke Wang (International Journal of Refrigeration, 2026)

An empirical study on the thermal environment improvement and energy conservation of high-reflective-evaporative composite roofs - Lina Jiang; Yunran Min; Jihui Yuan; Chaoqun Zhuang; Rui Guo; Jiayao Yu; Yafeng Gao (Building and Environment, 2026)

Preparation and characterization of Ag@MOF-Amomum tsaoko essential oil/waterborne polyurethane composite films for strawberry preservation - Yuyue Qin; Hongda Yu; Haiyan Chen; Yongliang Zhuang; Qiuming Liu; Rui Cui; Cong Zhang; Charles Brennan; Yuanxiang Huang (Food Control, 2025)

Dual-mechanism defect engineering of multi-enzyme embedded ZIF-8 for efficient anthocyanin extraction from black rice - Mengyuan Cao; Bicong Wang; Yuchao Deng; Da-Wei Pan; Xiao-Jie Ju; Rui Xie; Zhuang Liu; Xing-Long Zhou; Mao-Jie Zhang; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2025)

Single-cell–guided repositioning of Sorafenib enables nano-immunotherapy for scarless burn healing - Yue Tao; Huaxin Li; Jiaheng Xie; Rui Ding; Zhiwei Zhuang; Xu Yang; Yang Zhu; Jie Shan; Xu-lin Chen (Chemical Engineering Journal, 2025)

Effects of forest gaps on the humification process of deadwood in the subalpine forest - Zhuang Wang; Qin Wang; Rui Cao; Lifeng Wang; Wanqin Yang (CATENA, 2025)

The endogenous fungus Colletotrichum endophyticum from Korean epimedium Nakai promoted the growth of the model plant Arabidopsis thaliana - Jiang Rui; Zou Mingxuan; Liu Yucui; Zhuang Xin; Qi Xiaoting; Shi Fang; Liu Hanning; Xiao Jinglei (Archives of Microbiology, 2025)

In situ growth of NiCo2O4 nanosheets on N,S co-doped rice husk biochar for ultrasensitive and selective Pb2 + and Cd2+ electrochemical sensing - Mingmei Ge; Xinying Han; Rui Wang; Chenxi Wu; Shiyu Wang; Bao Chang; Zhuang Miao; Yang Zhao; Huan Wang (Journal of Environmental Chemical Engineering, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

Enhanced storability of fresh walnut kernels with zein/tea polyphenol/apple pectin coatings by layer-by-layer assembly technique - Wenwen Li; Wenwen Zhang; Dengjie Yao; Muxi Yang; Beibei Zhang; Yu Qin; Delu Ning; Yongliang Zhuang; Lirong Li; Rui Huang (Food Control, 2025)

A ratiometric fluorescent sensor based on Eu3 + -β-diketone functionalized covalent organic framework hybrid material-loaded in electrospun polyvinylidene fluoride film for ultra-sensitive and rapid detection of glyphosate - Yingfei Hui; Hao Guo; Rui Xue; Mingyue Wang; Yanyan Ma; Dengke Zhuang; Wu Yang (Journal of Hazardous Materials, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

The degradation of lignin and cellulose in typhoon-induced unsenescent leaf litter depends greatly on functional strategies among tree species - Rui Cao; Huaibin Wang; Lifeng Wang; Zhuang Wang; Zhihui Wang; Qin Wang; Naiyue Lv; Xu Wang; Wanqin Yang (Plant and Soil, 2025)

Log decomposition and forest gaps synergistically shape the structure and function of wood-inhabiting microbial communities in forest ecosystems - Qin Wang; Zhuang Wang; Josep Peñuelas; Rui Cao; Lifeng Wang; Wanqin Yang (Applied Soil Ecology, 2025)

Sesquiterpenoids isolated from the root bark of Lycium chinense - Xiao-xia Wang; Qian Liu; Ning Wang; Rui-li Zhang; Xiao Li; Peng-yu Zhuang; Hang Liu; Liang-dan Sun; Yang Jin (Phytochemistry, 2025)

Decaying logs and gap positions jointly maintain the structure and function of soil invertebrate community in a subalpine forest - Yurui Jiang; Zhuang Wang; Rui Cao; Qin Wang; Weizhong Li; Wanqin Yang (Plant and Soil, 2025)

Identification and bioactivity evaluation of ring-opening and lactone forms of enterolactone from sheep fed flaxseed cake - Cong-Cong Zhuang; Chun-Rui Liu; Hai-Yan Xu; Xin-Yue Yang; Dan-Dan Wu; Zhong Zheng; Li-Wei Wang; Zheng Liu; Chao-Mei Ma (Natural Product Research, 2025)

Study on the flame retarding mechanism of HFC-134a on hydrocarbon refrigerants - Rui Zhai; Xiang Li; Yuan Zhuang; Bin Ye; Xiangnong Liu; Qingqing Li; Lei Tang; Ke Wang (International Journal of Refrigeration, 2025)

Multi-shank flexible implantable neural interface for long-term olfactory neuron recording toward odor perception - Qunchen Yuan; Jiale Wang; Chunlian Qin; Shunuo Shang; Haoze Xu; Fan Wu; Yong Qiu; Haoting Zhang; Rui Sun; Ping Wang; Liujing Zhuang; Hao Wan (Chemical Engineering Journal, 2025)

The immediate effect of typhoon disturbance on soil carbon fractions along a subtropical forest gap gradient - Qingjun Ma; Rui Cao; Zhuang Wang; Qin Wang; Zhihui Wang; Lifeng Wang; Wanqin Yang (CATENA, 2025)

Effect of different zein/tea polyphenol/apple pectin coating on nutritional, physicochemical properties of fresh walnut kernel preservation - Wenwen Li; Yu Qin; Beibei Zhang; Wenwen Zhang; Dengjie Yao; Chunyin Zeng; Delu Ning; Yongliang Zhuang; Lirong Li; Rui Huang (Food Chemistry, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Knockdown of SETD5 Inhibits Colorectal Cancer Cell Growth and Stemness by Regulating PI3K/AKT/mTOR Pathway - Xiaohua Zhou; Wenqiang Chen; Duanming Zhuang; Guangqi Xu; Yongqiang Puyang; Hongqing Rui (Biochemical Genetics, 2025)

Functional characterization and site-directed mutagenesis of a novel UDP-glycosyltransferase from Panax japonicus var. major - Lu Mou; Yang Zhang; Yu-Xin Zhuang; Rui-Fang Ren; Ran Xu; Ling Yang; Shao-Peng Zhang; Deng-Xiang Du (Planta, 2025)

Space weathering characteristics of lunar permanently shadowed regions soils: Evidence from experimental simulation - Zixuan Han; Yang Li; Chen Li; Ronghua Pang; Sizhe Zhao; Zhuang Guo; Kairui Tai; Rui Li; Zhenhao Hu; Li Liu (Acta Geochimica, 2025)

Cross‐Continental Shifts of Ecological Strategy in a Global Plant Invader - Ramona E. Irimia; Weihan Zhao; Peipei Cao; Madalin Parepa; Zhi‐Yong Liao; Shengyu Wang; Jeannie M. Mounger; Conner Richardson; Fatima Elkott; Xin Zhuang; Jingwen Bi; Jieren Jin; et al. (Global Ecology and Biogeography, 2025)
Aim Plant invasions are a global problem that requires studying plants and their environmental associations across native and introduced ranges. Location 2000 km transects in China, Europe and North America. Time Period June 2019–July 2020. Major Taxa Studied Japanese knotweed ( Reynoutria japonica ). Methods We surveyed 150 populations of Japanese knotweed, a noxious invader of the temperate zone, along 2000 km transects in native China and the introduced ranges of Europe and North America. Results We found that larger plants and denser populations in the introduced ranges were associated with shifts in leaf economy and chemical defences. Introduced knotweed populations had higher SLA but reduced leaf chlorophyll, lignin, C:N ratio and leaf toughness along with altered leaf tannins, flavonoids and alkaloids. We found three distinct multivariate knotweed phenotypes primarily in the introduced ranges, and two multivariate knotweed phenotypes mainly in native populations. Main Conclusions Decreased herbivore and pathogen impacts in introduced populations and changes in environmental associations indicate that enemy release and novel habitat conditions might have driven the emergence of novel ecological strategies in this global plant invader.

Synthesis and multilayer hollow core–shell engineering of N-doped C@ZnFe2O4@polypyrrole microspheres with high performance microwave absorbing performance - Yuxia Shi; Rui Zhao; Xiangxiang Huang; Yingzan Zhuang; Qin Guo; Mingliang Ma; Tingxi Li; Yong Ma (Chemical Engineering Journal, 2025)

Towards resilient communities: Evaluating the nonlinear impact of the built environment on COVID-19 transmission risk in residential areas - Weiqi Guo; Jingwei Wang; Xiaoyu Liu; Zhenyu Pan; Rui Zhuang; Chunying Li; Haida Tang (Building and Environment, 2025)

Controllable construction of ratiometric fluorescent probe based on Ag/Au nanoclusters and silicon nanoparticles for multivariate detection of Ag+, Cu2+, and Hg2+ - Jingyu Pang; Linan Zhou; Zhuang Liang; Tingting Li; Rui Yan; Fang Chai (Journal of Environmental Chemical Engineering, 2024)

In situ generation of cuprous oxide in metal-organic framework for significantly enhanced room-temperature ammonia sensing: Synergy enabling excellent sensitivity and selectivity - Honglei Zhang; Zhuang Yan; Yue Ying; Fengbin Zheng; Rui Song; Zhiyong Tang; Yaling Liu (Journal of Environmental Chemical Engineering, 2024)

Vacuum-thermal alteration of lunar soil: Evidence from iron whiskers on troilite in Chang’e-5 samples - Chen Li; Yang Li; Kuixian Wei; Xiumin Chen; Kairui Tai; Zhuang Guo; Rui Li; Han Yu; Xiongyao Li; Wenhui Ma; Jianzhong Liu (Geochimica et Cosmochimica Acta, 2024)

A double-layer film based on the strategy of tannic acid-anthocyanin co-pigmentation and tannic-crosslinked-gelatin/−reduced Ag nanoparticles for beef preservation and monitoring - Rui Li; Haoyu Feng; Shancan Wang; Di Zhuang; Youhong Wen; Jie Zhu (Food Chemistry, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Pilot study to reconstruct life history of Diaphus thiollierei from the Arabian Sea by otolith microstructure and microchemistry - Lisheng Wu; Wenxin Zhuang; Qiaohong Liu; Rui Wang; Yuan Li; Longshan Lin; Shufang Liu; Shaoxiong Ding (Acta Oceanologica Sinica, 2024)

Rational design of chromium-doped NiFe phosphide/phosphate heterostructures for inhibiting chloride ion adsorption and achieving alkaline seawater splitting at industrial-level current density - Fanjia Sun; Yanhui Wang; Xueqing Tian; Rui Zhu; Ziliang Zhuang; Youbin Zheng; Jianbing Zang; Liang Dong (Chemical Engineering Journal, 2024)

High-throughput generation of monodisperse double emulsions via controllable symmetric splitting in Y-shaped microchannels - Lin-Ling Fan; Wei Wang; Xiao-Jie Ju; Zhuang Liu; Rui Xie; Jianhong Xu; Guangsheng Luo; Da-Wei Pan; Liang-Yin Chu (Chemical Engineering Journal, 2024)

Dialdehyde starch cross-linked aminated gelatin sponges with excellent hemostatic performance and biocompatibility - Yu-He Zhu; Chen-Yu Zhou; Xu Peng; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Xiao-Jie Ju; Liang-Yin Chu (Carbohydrate Polymers, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Combustion characteristics analysis and performance evaluation of a hydrogen engine under direct injection plus lean burn mode - Wei Chen; Chun Lu; Qingsong Zuo; Chuanfu Kou; Rui Shi; Hui Wang; Dezhong Ning; Zhuang Shen; Guohui Zhu (Journal of Cleaner Production, 2024)

Experimental and theoretical studies on the flame retarding performances of 1,3,3,3-tetrafluoro-1-propene - Rui Zhai; Xiang Li; Yuan Zhuang; Bin Ye; Zhao Yang; Xianhui Su; Binjian Nie (Fuel, 2024)

Decaying logs and gap positions jointly mediate the structure and function of soil bacterial community in the forest ecosystem - Qin Wang; Zhuang Wang; Josep Peñuelas; Rui Cao; Lifeng Wang; Wanqin Yang (Forest Ecology and Management, 2024)

Effects of carbonation modification on shear performance of recycled aggregate concrete beams: Test and mechanism analysis - Yingwu Zhou; Wenzhuo Xu; Jiahao Zhuang; Wenwei Lin; Feng Xing; Rui Hu (Engineering Structures, 2024)

Efficient elimination of antibiotic resistome in livestock manure by semi-permeable membrane covered hyperthermophilic composting - Bo Sun; Zhihui Bai; Rui Li; Manjiao Song; Jian Zhang; Jiancheng Wang; Xuliang Zhuang (Bioresource Technology, 2024)

An emerging antibacterial nanovaccine for enhanced chemotherapy by selectively eliminating tumor-colonizing bacteria - Linfu Chen; Zheyu Kang; Jingjing Shen; Rui Zhao; Yu Miao; Lin Zhang; Zixuan Zheng; Zhemin Zhang; Nanhui Liu; Cheng Wang; Huapan Fang; Jun Zhou; et al. (Science Bulletin, 2024)

Impact-dispersed Fe–Fe1−S core–shell particles in Chang’e-5 lunar soil impact glass - Chen Li; Yang Li; Kuixian Wei; Zhuang Guo; Rui Li; Xiongyao Li; Jianzhong Liu; Wenhui Ma (Geochimica et Cosmochimica Acta, 2024)

A lightweight and efficient hollow sunken carbon@MnO2/reduced graphene oxide composite for high-performance electromagnetic wave absorption - Yuxia Shi; Baoquan Liang; Hong Gao; Rui Zhao; Yingzan Zhuang; Qin Guo; Xianhan Shao; Hankun Wang; Mingliang Ma; Tingxi Li; Yong Ma (Chemical Engineering Journal, 2024)

Unlocking energy and economic benefits of integrated green envelopes in office building retrofits - Rui Guo; Yunran Min; Yafeng Gao; Xiangjie Chen; Huizhong Shi; Changqiao Liu; Chaoqun Zhuang (Building and Environment, 2024)

Formation and growth of nanophase iron particles on the surface of Mercury revealed by experimental study - Ronghua Pang; Yang Li; Chen Li; Pengfei Zhang; Zhuang Guo; Sizhe Zhao; Han Yu; Li Wang; Chenxi Zhu; Shuangyu Wang; Kairui Tai; Qinwei Zhang; et al. (Acta Geochimica, 2024)

A colorimetry-enhanced tri-functional film with high stability by polyphenol-anthocyanin co-pigmentation/conjugate: New prospect for active intelligent food packaging - Rui Li; Haoyu Feng; Shancan Wang; Di Zhuang; Jie Zhu (Food Chemistry, 2024)

Modern pollen-vegetation relationships along altitudinal vegetation belts in the Leigong Mountain of southwestern China - Shuming Li; Wenwei Zhao; Lisi Wei; Weihe Ren; Qinran Gu; Siqi Wu; Yang Ji; Ziteng Yang; Rui Zhuang; Chunzhu Chen (Journal of Mountain Science, 2024)

SERS detection of triazole pesticide residues on vegetables and fruits using Au decahedral nanoparticles - Zhinan Chen; Rui Tan; Mei Zeng; Xue Yuan; Kaiyi Zhuang; Changsheng Feng; Yi He; Xiaojun Luo (Food Chemistry, 2024)

Valorization of Nannochloropsis oceanica for integrated co-production of violaxanthin cycle carotenoids - Rui Yin; GengJie Zhuang; Yuhui Lei; Jichang Han; Yanrong Li; Jinrong Zhang; Xiaojun Yan (Bioresource Technology, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Succinylated acetyl-CoA carboxylase contributes to aflatoxin biosynthesis, morphology development, and pathogenicity in Aspergillus flavus - Rui Xie; Bei Zhang; Elisabeth Tumukunde; Zhenhong Zhuang; Jun Yuan; Shihua Wang (International Journal of Food Microbiology, 2024)

De-branching of starch molecules enhanced the complexation with chitosan and its potential utilization for delivering hydrophobic compounds - Min Liu; Min Zhuang; Dengdeng Li; Jinxu Fan; Rui Wang; Xuanyu Wang; Sheng Ke; Ming Ning; Zhongkai Zhou (Food Hydrocolloids, 2024)

Purification and Characterization of a Novel Anticoagulant Peptide from Protein Hydrolysate of Eupolyphaga sinensis Walker - Xidong Li; Xuefei Zhuang; Huifen Li; Linmei Pan; Rui Liu; Huaxu Zhu; Zhishu Tang (International Journal of Peptide Research and Therapeutics, 2024)

An experimental and modeling study on the oxidation of ammonia-methanol mixtures in a jet stirred reactor - Yuan Zhuang; Ruikang Wu; Xinyan Wang; Rui Zhai.; Changyong Gao (Fuel, 2024)

An intelligent chitosan/gelatin film via improving the anthocyanin-induced color recognition accuracy for beef sub-freshness differentiation monitoring - Rui Li; Shancan Wang; Haoyu Feng; Di Zhuang; Jie Zhu (Food Hydrocolloids, 2024)

Induced mechanism of phosphatase hormesis by Cd ions and rhizosphere metabolites of Trifolium repens L. - Chenxi Zhang; Haibo Li; Yue Yang; Xulun Zhou; Damiao Zhuang; Wengang Liu; Kaixuan Wang; Pengkai Wang; Wenxin Zhang; Yaran Bai; Haotian Ma; Bingqian Gao; et al. (Chemosphere, 2023)

Reaction behavior of sulfides in blast furnace raw materials under hydrogen-rich reducing atmosphere - Zhuang Zheng; Yang You; Rui Wang; Zhixiong You; Jie Dang; Xuewei Lv (Fuel, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Genome resequencing reveals the population structure and genetic diversity of almond in Xinjiang, China - Pengyu Wu; Dong Li; Rui Zhuang; Hao Zuo; Zhiyong Pan; Bo Yang; Chongzhi Xu (Genetic Resources and Crop Evolution, 2023)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

Mechanistic research on the complex motion response of a TLP in a tender-assisted drilling state - Zhuang Kang; Rui Chang; Wei Meng (Ocean Engineering, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

High-temperature oxidation and a comprehensive kinetic mechanism of HFO-1234yf - Rui Zhai; Siwei Tan; Yuan Zhuang; Bin Ye; Yongjie Shi (International Journal of Refrigeration, 2023)

Effects of the launch parameters on trans-phase stability performance and mechanism for submarine-launched missiles model - Qibin Zhuang; Huanbin Zhang; Chenhong Zhao; Xingyu He; Yu Liu; Zhirong Liu; Shuping Li; Rui Zhu; Dezhi Wu (Ocean Engineering, 2023)

Dual-layer drug release system based on ureteral stents inhibits the formation of ureteral stricture - Zhiduan Cai; Wenjun Luo; Haoquan Zhuang; Congling Ren; Xiaolin Pan; Yuyu Xu; Haoran Wang; Xiezhao Li; Yaoji Yuan; Rui Zhu; Xiangyu Zhan; Lin Jin; et al. (Chemical Engineering Journal, 2023)

Sustained-release behavior and the antitumor effect of charge-convertible poly(amino acid)s drug-loaded nanoparticles - Zhuang Hu; Gongshu Wang; Rui Zhang; Yingyu Yang; Jiwei Wang; Jianshe Hu; Aikebaier Reheman (Drug Delivery and Translational Research, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Experimental and theorical study on the pyrolysis behaviors of 2,3,3,3-tetrafluroropropene - Rui Zhai; Yuan Zhuang; Siwei Tan; Jingchun Tang (Journal of Fluorine Chemistry, 2023)

Novel “all-in-one” multifunctional gelatin-based film for beef freshness maintaining and monitoring - Rui Li; Di Zhuang; Haoyu Feng; Shancan Wang; Jie Zhu (Food Chemistry, 2023)

Correction: Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

The distribution and emission of CO2, CH4 and light hydrocarbons in an anticyclonic eddy of the Kuroshio extension - Xiao-Jun Li; Jian Wang; Hao Qiao; Rui-Chen Zhu; Hong-Hai Zhang; Zhao-Hui Chen; Andrew Montgomery; Shan Zheng; Guang-Chao Zhuang (Frontiers in Marine Science, 2023)
Mesoscale eddies are energetic and swirling circulations that frequently occur in the open ocean. The effects of mesoscale eddies on the biogeochemical cycling of climate-relevant gases remain poorly constrained. We investigated the distribution and air-sea fluxes of CO 2 , methane, and five non–methane hydrocarbons (NMHCs) in an anticyclone eddy of Kuroshio Extension during September 2019. Within eddy core, intense stratification hindered the replenishment of nutrients and favored the growth of small-size phytoplankton, such as Prochlorococcus . Seawater pCO 2 decreased from 406.1 μatm at the eddy outside to 377.5 μatm at the eddy core, accompanied by a decrease in surface seawater temperature from 26.7 °C to 25.2 °C. The vertical distribution of methane (0.3-9.9 nmol L -1 ) was influenced by the eddy process, with a maximum at 80 m in the eddy core, which might be attributed to the degradation of phosphonates sustained by Prochlorococcus . The concentrations of five NMHCs (ethane, ethylene, propane, propylene, and isoprene) ranged from 17.2-126.2, 36.7-168.1, 7.5-29.2, 22.6-64.1, 54.5-172.1, 3.5-27.9 pmol L -1 , respectively. Isoprene correlated well with Chl- a concentrations at the eddy core, while no significant correlation was observed at the eddy outside. Air-sea fluxes of CO 2 and isoprene associated with the eddy core were higher than those of the eddy outside, while the maximum ventilation of methane and other NMHCs (ethane, ethylene, propane, and propylene) was found at the eddy outside. Collectively, physical processes such as eddies impact the production and distribution of light hydrocarbons in seawater and further influence their regional emissions to the atmosphere.

Exogenous methyl jasmonate and cytokinin antagonistically regulate lignin biosynthesis by mediating CsHCT expression in Camellia sinensis - Chun-Fang Liu; Ni Yang; Rui-Min Teng; Jing-Wen Li; Yi Chen; Zhi-Hang Hu; Tong Li; Jing Zhuang (Protoplasma, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

Study of water and hydrogen addition on the pyrolysis and combustion characteristics of isooctane - Yuan Zhuang; Changyong Gao; Rui Zhai; Ruikang Wu (Fuel, 2023)

Characteristics and intrinsic influencing factors of log humification depend on wood traits in a subalpine forest - Zhuang Wang; Qin Wang; Bo Tan; Chenhui Chang; Lifeng Wang; Rui Cao; Yurui Jang; Jörg Müller; Wanqin Yang (CATENA, 2023)

Forest gaps accelerate the degradation of cellulose and lignin in decaying logs in a subalpine forest - Zhuang Wang; Bo Tan; Wanqin Yang; Qin Wang; Chenhui Chang; Lifeng Wang; Han Li; Chengming You; Rui Cao; Yurui Jiang; Jörg Müller (European Journal of Forest Research, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Flow-drag reduction performance of a resident electrolytic microbubble array and its mechanisms - Rui Zhu; Huanbin Zhang; Weiqi Wen; Xingyu He; Chenhong Zhao; Yu Liu; Qibin Zhuang; Zhirrong Liu (Ocean Engineering, 2023)

Habitat quality dynamics in China's first group of national parks in recent four decades: Evidence from land use and land cover changes - Xin Chen; Le Yu; Yue Cao; Yidi Xu; Zhicong Zhao; Youbo Zhuang; Xuehua Liu; Zhenrong Du; Tao Liu; Bo Yang; Lu He; Hui Wu; et al. (Journal of Environmental Management, 2023)

Fluoroalkane modified cationic polymers for personalized mRNA cancer vaccines - Junyan Li; Yuanyuan Wu; Jian Xiang; Hairong Wang; Qi Zhuang; Ting Wei; Zhiqin Cao; Qingyang Gu; Zhuang Liu; Rui Peng (Chemical Engineering Journal, 2023)

Microfluidic emulsification techniques for controllable emulsion production and functional microparticle synthesis - Wei Wang; Bing-Yu Li; Mao-Jie Zhang; Yao-Yao Su; Da-Wei Pan; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Yousef Faraj; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Spatial heterogeneity of greenhouse gas emissions from cereal crop production in China - Minghao Zhuang; Dario Caro; Wei Qin; Chun Wang; Xiaolin Yang; Rui Liu; Lin Zhang (Environmental Chemistry Letters, 2022)

Environmental and economic benefits of substituting chemical potassium fertilizer with crop straw residues in China - Junhui Yin; Dongjia Li; Jingyao Yu; Xin Bai; Wenjing Cui; Rui Liu; Minghao Zhuang (Environmental Science and Pollution Research, 2022)

Spatial-temporal distribution and tectonic setting of Mesozoic W-mineralized granitoids in the Xing-Meng Orogenic Belt, NE China - Wei Xie; Qing-Dong Zeng; Rui-Liang Wang; Jin-Jian Wu; Zhe-Ming Zhang; Feng-Chun Li; Zhuang Zhang (International Geology Review, 2022)

Establishment and optimization of PEG-mediated protoplast transformation in the microalga Haematococcus pluvialis - Chunli Guo; Muhammad Anwar; Rui Mei; Xinyi Li; Di Zhao; Yanan Jiang; Jieyi Zhuang; Chen Liu; Chaogang Wang; Zhangli Hu (Journal of Applied Phycology, 2022)
Genetic manipulation of Haematococcus pluvialis is difficult because of the lack of a stable and convenient transformation system. The pH124-EGFP-Ble vector containing ble as a selective gene and EGFP as a reporter gene was constructed and employed for effective transformation. H. pluvialis protoplasts were obtained by treating with cellulase and macerozeme. Then polyethylene glycol-mediated transformation was established by incubating the protoplast with the vector. To improve the transformation efficiency of H. pluvialis protoplasts, the transformation system was optimized in consideration of different influencing factors, including zeomycin concentration, growth stage, amount of transformed vector, linearization of the vector, and duration of low-intensity illumination. The integration and expression of ble and EGFP was confirmed in the transformants. Moreover, the optimal combination for protoplast transformation of H. pluvialis was determined to be 5 µg of the linearized vector used to transform cells in the log growth phase, and then the transformed protoplasts allowed to recover under low-intensity illumination for 6 h. This study represents and describes the successful development of an H. pluvialis transformation protocol using protoplasts, which will enable convenient genetic manipulation of this important algal species.

Identification and Expression Analysis of the SBP-box Gene Family Related to Abiotic Stress in Tea Plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Hao Liu; Yu Wang; Jing Zhuang (Plant Molecular Biology Reporter, 2022)

Characteristics of seismic and acoustic signals of rock falls: an experimental study - Zheng-Yi Feng; Rui-Chia Zhuang (Landslides, 2021)

Construction and application of easy-to-detect cyanobacteria with vp28 gene - Min-Min Zhuang; Wen Peng; Yang Xu; Xiao-Hui Jia; Ding-Ji Shi; Pei-Min He; Rui Jia (Journal of Applied Phycology, 2021)

Carbonate diagenetic facies of Yijianfang Formation (Shunbei area, Tarim Basin, Southeastern China) - Chuanjie Cheng; Chongyang Wu; Bingsong Yu; Weili Yang; Jun Liu; Rui Zhao; Zhuang Ruan (Arabian Journal of Geosciences, 2021)

Paenibacillus puerhi sp. nov., isolated from the rhizosphere soil of Pu-erh tea plants (Camellia sinensis var. assamica) - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Xing-Hua Wang; Wen-Jie Zhang; Li Zhuang; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

A Rehmannia glutinosa cinnamate 4-hydroxylase promotes phenolic accumulation and enhances tolerance to oxidative stress - Yan Hui Yang; Heng Yang; Rui Fang Li; Cui Xiang Li; Lei Zeng; Chao Jie Wang; Na Li; Zhuang Luo (Plant Cell Reports, 2021)

Identification and expression analysis of caffeoyl-coenzyme A O-methyltransferase family genes related to lignin biosynthesis in tea plant (Camellia sinensis) - Shi-Jia Lin; Ya-Zhuo Yang; Rui-Min Teng; Hao Liu; Hui Li; Jing Zhuang (Protoplasma, 2021)

Effects of shading on lignin biosynthesis in the leaf of tea plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Shi-Jia Lin; Hao Liu; Jing Zhuang (Molecular Genetics and Genomics, 2021)

Effects of Epixylic Vegetation Removal on the Dynamics of the Microbial Community Composition in Decaying Logs in an Alpine Forest - Chenhui Chang; Fuzhong Wu; Zhuang Wang; Bo Tan; Rui Cao; Wanqin Yang; Johannes H. C. Cornelissen (Ecosystems, 2019)

Temperature-control-induced masculinization in tiger puffer Takifugu rubripes - He Zhou; Zixin Zhuang; Rui Zhang; Qizheng Xu; Yuting Liang; Zhiqiang Jiang; Xia Li; Tianyu Ma; Yajuan Li (Journal of Oceanology and Limnology, 2019)

Identification of genes revealed differential expression profiles and lignin accumulation during leaf and stem development in tea plant (Camellia sinensis (L.) O. Kuntze) - Yong-Xin Wang; Rui-Min Teng; Wen-Li Wang; Ying Wang; Wei Shen; Jing Zhuang (Protoplasma, 2019)

The adaptability of a wetland plant species Myriophyllum aquaticum to different nitrogen forms and nitrogen removal efficiency in constructed wetlands - Rui Wang; Na Bai; Shengjun Xu; Guoqiang Zhuang; Zhihui Bai; Zhirui Zhao; Xuliang Zhuang (Environmental Science and Pollution Research, 2018)

Polyamine-binding protein PotD2 is required for stress tolerance and virulence in Actinobacillus pleuropneumoniae - Zhuang Zhu; Qin Zhao; Yu Zhao; Fei Zhang; Xintian Wen; Xiaobo Huang; Yiping Wen; Rui Wu; Qigui Yan; Yong Huang; Xiaoping Ma; Xinfeng Han; et al. (Antonie van Leeuwenhoek, 2017)

Cold-Inducible Protein RBM3 Protects UV Irradiation-Induced Apoptosis in Neuroblastoma Cells by Affecting p38 and JNK Pathways and Bcl2 Family Proteins - Rui-Juan Zhuang; Jian Ma; Xiang Shi; Fei Ju; Shuang-Ping Ma; Lei Wang; Bin-Feng Cheng; Yan-Wen Ma; Mian Wang; Tong Li; Zhi-Wei Feng; Hai-Jie Yang (Journal of Molecular Neuroscience, 2017)

Comprehensive Analysis of R2R3-MYB Genes During Adventitious Root Formation in Cuttings of Morus alba - Xiao Long Du; Xu Cao; Chao Rui Yin; Zhuang Tang; Wei Du; Yue Yuan Ban; Jia Ling Cheng (Journal of Plant Growth Regulation, 2017)

Dietary Zinc Oxide Modulates Antioxidant Capacity, Small Intestine Development, and Jejunal Gene Expression in Weaned Piglets - Cui Zhu; Hang Lv; Zhuang Chen; Li Wang; Xiuju Wu; Zhongjian Chen; Weina Zhang; Rui Liang; Zongyong Jiang (Biological Trace Element Research, 2017)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

Atrokylindriopsis, a new genus of hyphomycetes from Hainan, China, with relationship to Chaetothyriales - Ying-Rui Ma; Ji-Wen Xia; Jian-Mei Gao; Xiang-Yu Li; Rafael F. Castañeda Ruíz; Xiu-Guo Zhang; Zhuang Li (Mycological Progress, 2015)

Characterization of 15 polymorphic microsatellite loci for the jellyfish Rhopilema esculentum - Ling Zhu; Ao-ao Yang; Chun-ya Zhou; Hong Yang; Xiao-rui Luo; Si-Qing Chen; Zhi-meng Zhuang (Conservation Genetics Resources, 2015)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Integrated application of 3D seismic and microseismic data in the development of tight gas reservoirs - Rui-Zhao Yang; Zheng-Guang Zhao; Wei-Jun Peng; Yu-Bo Gu; Zhan-Gang Wang; Xi-Qin Zhuang (Applied Geophysics, 2013)

Characterization of a novel isoform of the human ORMDL3 gene - Rui Jin; Wen-Xiao Yuan; Hua-Guo Xu; Wei Ren; Li-Li Zhuang; Guo-Ping Zhou (Cell and Tissue Research, 2011)

Bioenergy Sustainability in China: Potential and Impacts - Jie Zhuang; Randall W. Gentry; Gui-Rui Yu; Gary S. Sayler; John W. Bickham (Environmental Management, 2010)

Effects of rice cropping intensity on soil nitrogen mineralization rate and potential in buried ancient paddy soils from the Neolithic Age in China’s Yangtze River Delta - Jia Lu; Zhengyi Hu; Zhihong Xu; Zhihong Cao; Shunyao Zhuang; Linzhang Yang; Xiangui Lin; Yuanhua Dong; Rui Yin; Jinlong Ding; Yunfei Zheng (Journal of Soils and Sediments, 2009)

Root water uptake and profile soil water as affected by vertical root distribution - Gui-Rui Yu; Jie Zhuang; Keiichi Nakayama; Yan Jin (Plant Ecology, 2007)

A coupled model of photosynthesis-transpiration based on the stomatal behavior for maize (Zea mays L.) grown in the field - Gui-Rui Yu; Tatsuaki Kobayashi; Jie Zhuang; Qiu-Feng Wang; Le-Qing Qu (Plant and Soil, 2003)